Why Geography in Poland Has Never Radicalized: Political and International Entanglements of Polish Geography Seen Through the Prism of Antoni Kukliński’s Professional Trajectory - Zarycki, Tomasz (Serendipities. Journal for the Sociology and History of the Social Sciences, 2021)
This paper deals with the role of social sciences, and more specifically of geography and regional planning, in the legitimization of European integration and neo-liberal economic and social reforms introduced since 1989 in Poland and, more broadly, in post-communist Central and Eastern Europe. Using the example of an intellectual biography of Antoni Kukliński, one of the most prominent Polish geographers, the role of the old intelligentsia elite and its American professional experiences in the evolution of the Polish academia is also analyzed, as well as its involvement in the first non-communist government. The paper also discusses the absence of critical schools within the field of Polish geography as well as other disciplines of social sciences. This is done though the reconstruction of the basic structure of the given academic field and its evolution over time from late communist period to present days. This specific structure of the field of Polish geography, which as it is argued is similar to other fields of social sciences and humanities in Poland, also helps to better contextualize the trajectory of Kukliński.